A new index for assessing cerebral ventricular volume in idiopathic normal-pressure hydrocephalus: a comparison with Evans’ index - He, Wenjie; Fang, Xuhao; Wang, Xiaowei; Gao, Pan; Gao, Xing; Zhou, Xi; Mao, Renling; Hu, Jiani; Hua, Yanqing; Xia, Jun (Neuroradiology, 2020)
Purpose To recommend a new simple and explicit index termed the anteroposterior diameter of the lateral ventricle index (ALVI) for assessing brain ventricular size in neuroimaging and to compare Evans index (EI) between idiopathic normal pressure hydrocephalus (iNPH) patients and age-matched healthy elderly subjects. Methods Retrospective measurements of ventricular volume (VV), relative VV (RVV), the EI, and the ALVI were taken from thin-section CT scans for 23 pre-shunt-insertion iNPH patients and 62 age-matched healthy elderly volunteers. The area under the receiver operating characteristic (ROC) curve (AUC), net reclassification improvement (NRI), and integrated discrimination improvement (IDI) were calculated to assess the effectiveness of ALVI scores for predicting VV. Results The correlations between VV or RVV and ALVI scores (VV, r = 0.957; RVV, r = 0.983) were significantly stronger than the corresponding correlations with EI scores (VV, r = 0.843; RVV, r = 0.840). The AUC for ALVI scores was significantly greater than the AUC for EI scores. Furthermore, with the inclusion of the ALVI, the NRI value was 0.14 and the IDI value was 0.14; these improvements were also statistically significant. Conclusion The ALVI is a more accurate and more explicitly defined marker of VV than the EI and assesses ventricular enlargement effectively. We suggest that ventricular enlargement of the healthy elderly be defined by ALVI > 0.50.